Reformasi Kelembagaan Unit Pengawas Internal: Mengatasi Desentralisasi Korupsi - Aulia, Sandra; Ridwan Maksum, Irfan (Jurnal Ilmiah Administrasi Publik, 2022)
Decentralization has led to the shift of corruption to the local level, as evidenced by number of corruption cases at the local governments. The phenomenon indicates the ineffectiveness of the local government's internal audit institutions that should play a role in preventing corruption. This study aims to analyze institutional reforms in the public sector’s internal audit system to effectively prevent the decentralization of corruption. Study of the literature, from previous theories and research, is applied as research methodology. The study found that the reforms, carried out by the internal audit institution to effectively prevent the decentralization of corruption, were carried out through regulatory reform, leadership reform, cultural reform, meritocracy reform and participation reform. This research contributes to the development of theory to strengthen the alignment of public management reforms, in terms of control through the effectiveness of the government's internal audit institutions, and provides input to optimize the duties and functions of the institutions to prevent corruption.